A higher FIB‐4 index is associated with an increased incidence of renal failure in the general population. Issue 12 (4th October 2022) - Schleicher, Eva Maria; Gairing, Simon Johannes; Galle, Peter Robert; Weinmann‐Menke, Julia; Schattenberg, Jörn M.; Kostev, Karel; Labenz, Christian
Abstract: The Fibrosis‐4 index (FIB‐4) is a recommended noninvasive fibrosis test in patients at risk of liver fibrosis. Chronic liver diseases are often associated with kidney diseases. This study aimed to investigate the association between FIB‐4 and the development of renal failure among the general population. For this study, we used the Disease Analyzer database, which includes diagnoses and basic medical and demographic data of patients followed in general practices in Germany. Using these data, we extensively matched patients with a FIB‐4 index ≥ 1.3 (n = 66, 084) to patients with a FIB‐4 index < 1.3 (n = 66, 084). The primary outcome was the incidence of renal failure or chronic renal failure during a 10‐year period. Within 10 years of the index date, 9.2% of patients with a FIB‐4 < 1.3 and 10.6% of patients with a FIB‐4 ≥ 1.3 were diagnosed with renal failure ( p  = 0.007). The endpoint chronic renal failure was reached by 7.9% with a FIB‐4 < 1.3 and 9.5% with a FIB‐4 ≥ 1.3 ( p  < 0.001). A FIB‐4 index ≥ 1.3 was associated with a slight increase in renal failure incidence (hazard ratio [HR]: 1.08, p  = 0.009). There was an increasing association between an increase in FIB‐4 index and the incidence of renal failure with the strongest association for a FIB‐4 index ≥ 2.67 (HR: 1.34, p  = 0.001). In sensitivity analyses, a significant association was found for the age group of 51–60 years (HR: 1.38, p  < 0.001), patients with arterial hypertension (HR: 1.15, p  < 0.001), obese patients (HR: 1.25, p  = 0.005), and patients with lipid metabolism disorders (HR:1.22, p  < 0.001). Conclusion : A higher FIB‐4 index is associated with an increased incidence of renal failure. Therefore, the FIB‐4 index may be useful in identifying patients who are at risk not only for liver‐related events but also for renal disease.